HUBUNGAN KEMAMPUAN LITERASI SAINS DAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Parinduri, Wina Mariana; Rajagukguk, Kiki Pratama; Rambe, Nurhamimah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The research objective was to find out how the critical thinking skills and literacy skills of elementary school students relate. The research method used is a correlational research method with a quantitative approach. Aims to reveal the relationship between variables. Population to be studied (Sugiyono, 2019). The population in this study were 215 fifth grade elementary school students consisting of 8 schools. The sampling technique used by researchers is simple random sampling technique. The sample of this research is 140 students. Data collection techniques in this study were in the form of tests of critical thinking skills and tests of scientific literacy abilities. The data processing carried out consisted of three stages, namely data description and categorization, analysis prerequisite testing, and hypothesis testing. Based on the research that has been done, it can be concluded that: 1) There is a relationship between scientific literacy abilities and students' critical thinking skills with a correlation coefficient of 0.368; 2) Scientific literacy ability influences or contributes to students' critical thinking skills by 13.6%; 3) Scientific literacy ability has a positive and significant relationship to students' critical thinking skills with a significance value based on a simple linear regression test <5%.